Adsorption and Kinetic Study of NI (II) Ions from Aqueous Solution using Natural Syrian Zeolite (Global Journal of Science Frontier Research, 2016)
Adsorption of Ni(II) ions from aqueous solution using natural Syrian zeolite has been studied. Batch shaking adsorption experiments were performed in order to determined the effects of contact time, pH and initial concentration on removal process. The experimental equilibrium data were tested for the Langmuir and Freundlish isotherms. It was determined that removal of Ni(II) ions was well fitted by pseudo-first order kinetic model. The adsorption involves a film diffusion, an intra-particle diffusion and a chemical ion-exchange between Na + ions of adsorbent and the Ni 2+ ions. The adsorption is endothermic and spontaneous process under studied conditions.
Keywords: adsorption; zeolite; Ni(II) ions